Situation Report: Romania, 10 April 1975 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
An information bulletin produced by Radio Free Europe based on extensive monitoring of communist bloc news outlets and primarily intended for internal circulation. Pieces were generally contributed by the staff of the research and analysis departments and treated current affairs in the region. Trade Agreement with US Signed Granting MFN Status to Romania Second Romanian-Yugoslav Power Plants to Be Built on Danube Relations with Developing Countries Ceausescu Begins Extended Foreign Tour with Visit to Japan National Youth Meetings to Be Held in November Publishing System Reorganized